EXPLORING PATIENT KNOWLEDGE AND CONCERNS ABOUT ANESTHESIOLOGY IN SAUDI ARABIAN ELECTIVE SURGERY SETTINGS (CAHIERS MAGELLANES-NS, 2024)
Introduction: Anesthesia, a cornerstone of modernist smedicine since 1846, has revolutionized surgical practice. Despite its crucial role, studies worldwide reveal inadequate public knowledge about anesthesia and anesthesiologists' multifaceted functions. In Saudi Arabia, where anesthesiology was established in 1956, limited research exists on patients' understanding and perceptions of anesthesia, particularly for elective surgeries. Recent studies in the region indicate low levels of anesthetic knowledge and significant patient concerns. Our study aims to assess knowledge level toward anesthesia and anesthesiologist role during surgery and to determine the concerns and misconceptions about anesthesia among patients undergoing elective surgeries in Saudi Arabia.Methodology: This is a cross-sectional study conducted from July to November 2024 using an online self-administrated questionnaire. Participants were patients over 18 years old undergoing elective surgery in Saudi Arabia, excluding emergency cases, healthcare personnel, Health specialties students, and those with cognitive disorders. The minimum sample size is 383, calculated using Raosoft with a 5% margin of error and 95% confidence interval. Data was collected via an anonymous Arabic questionnaire, previously validated in a Nigerian study, assessing knowledge, perceptions, and concerns about anesthesia and anesthesiologists' roles.Results: The study examined patient knowledge and concerns about anesthesiology in elective surgery settings in Saudi Arabia, involving 412 participants. The findings revealed a demographic skew towards females (70.9%) and a majority of Saudi nationals (95.1%). Although 94.9% recognized the term "anesthetist," only 21.1% understood their role in the operating room, highlighting a significant knowledge gap. Notably, 43.7% were unaware of which anesthetist administered their anesthesia, indicating a need for improved patient education. Concerns about post-operative pain (61.9%) and general anesthesia effects (38.6%) were prevalent, emphasizing the necessity for enhanced communication and transparency to alleviate patient fears.Conclusion: This study shows gap in patient knowledge and concerns regarding anesthesia in elective surgery settings in Saudi Arabia. The findings underscore the urgent need for targeted educational interventions to enhance patient understanding of anesthesia and the role of anesthesiologists.Introduction: Anesthesia, a cornerstone of modernist smedicine since 1846, has revolutionized surgical practice. Despite its crucial role, studies worldwide reveal inadequate public knowledge about anesthesia and anesthesiologists' multifaceted functions. In Saudi Arabia, where anesthesiology was established in 1956, limited research exists on patients' understanding and perceptions of anesthesia, particularly for elective surgeries. Recent studies in the region indicate low levels of anesthetic knowledge and significant patient concerns. Our study aims to assess knowledge level toward anesthesia and anesthesiologist role during surgery and to determine the concerns and misconceptions about anesthesia among patients undergoing elective surgeries in Saudi Arabia.Methodology: This is a cross-sectional study conducted from July to November 2024 using an online self-administrated questionnaire. Participants were patients over 18 years old undergoing elective surgery in Saudi Arabia, excluding emergency cases, healthcare personnel, Health specialties students, and those with cognitive disorders. The minimum sample size is 383, calculated using Raosoft with a 5% margin of error and 95% confidence interval. Data was collected via an anonymous Arabic questionnaire, previously validated in a Nigerian study, assessing knowledge, perceptions, and concerns about anesthesia and anesthesiologists' roles.Results: The study examined patient knowledge and concerns about anesthesiology in elective surgery settings in Saudi Arabia, involving 412 participants. The findings revealed a demographic skew towards females (70.9%) and a majority of Saudi nationals (95.1%). Although 94.9% recognized the term "anesthetist," only 21.1% understood their role in the operating room, highlighting a significant knowledge gap. Notably, 43.7% were unaware of which anesthetist administered their anesthesia, indicating a need for improved patient education. Concerns about post-operative pain (61.9%) and general anesthesia effects (38.6%) were prevalent, emphasizing the necessity for enhanced communication and transparency to alleviate patient fears.Conclusion: This study shows gap in patient knowledge and concerns regarding anesthesia in elective surgery settings in Saudi Arabia. The findings underscore the urgent need for targeted educational interventions to enhance patient understanding of anesthesia and the role of anesthesiologists.